The Japanese influence in Malaysian automotive industry: human resources management and development practices - Rashid, Abdullah; Jusoff, Kamaruzaman; Ahmad, Zalena; Takahashi, Yoshi (Canadian Research & Development Center of Sciences and Cultures, 2009)
This paper empirically examined the level of Japanese work organization and management techniques as practiced in PROTON. It has been argued that the Japanese work organization has been practiced and transferred more successful in the automobile industry because of its higher technicality. The PROTON-MITSUBISHI alliance has now been going for more than two decades (since 1982). Although PROTON has not yet been able to produce its own engine unless the CamPro engine with Waja model in 1999, this alliance is the best case to test the extent Japanese work organization is practiced to test the degree of transfer in the best sector and the best project to be studied. The discussion on Japanese influence on PROTON manufacturing systems to access the role of technological transfer done by Mitsubishi Motor Company (MMC) were well deliberated.